Generation of retractive spine circuits in the process of vitamin B12 deficiency - Mucha, Patrycja; Leksa, Natalia; Aebisher, David; Galiniak, Sabina; Bartosz, Seweryn; Leksa, Dawid; Bartusik-Aebisher, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Subacute degeneration of the posterior and lateral spinal cord is a rare neurological complication of B12 avitaminosis. Aim. In this paper, we present the case of a 65-year-old man who, in the course of long-term vitamin B12 deficiency associated with atrophic gastritis, developed a severe set of neurological symptoms that are part of the retinal spinal cord degeneration with characteristic features in MR imaging of the cervical spine in the form of an inverted “V mark” ‘in axial images and typical localization in the spinal cord. Description of the case. After careful analysis of the syndrome and making an early diagnosis, parenteral vitamin B12 supplementation began, resulting in improved neurological status, laboratory parameters as well as regression of changes in magnetic resonance imaging. Conclusion Significant symptoms of this syndrome are paresthesia in the distal parts of the limbs, ataxia, spastic paresis.
Keywords: ataxia; B12 avitaminosis; retinal spinal cord degeneratio